Wag the Dog A Study on Film and Reality in the Digital Age - Thanouli, Eleftheria (Bloomsbury Academic, 2013)
Wag the Dog became a media event and a cultural icon because it inadvertently short-circuited the distance that is  supposed to separate reality and fiction. The examination of the historical and social context in which it was  produced, exhibited and received worldwide enables the author to illuminate a series of changes in the way a fiction film reflects and  interacts with reality, urging us to reconsider some of our central and  long-standing concepts or even paradigms in film theory. Eleftheria  Thanouli provides new insights into a series of issues from both  classical and contemporary film theory, such as the conceptual and  ontological stakes in the use of digital technology, the impact of mass  media on public memory and the political role of cinema in a globalized  and conglomerated world.